The Implementation of Interpersonal Communication on the Adaptation of Students from Outside Makassar in Business English Communication Program - Saputra, Allan; Sunusi, Seny Luhriyani; Novia, Lely (Journal of Excellence in English Language Education, 2025)
This research aims to find out the implementation of interpersonal communication can affect the adaptation process of students outside Makassar in the Business English Communication study program and factors that influence the ability of students outside Makassar to adapt. This research uses a descriptive qualitative research design with the data obtained is in the form of explanations and descriptions. Data collection techniques using interviews and the instrument is interview guide. The results of this study indicate that the role of interpersonal communication is very influential on the adaptation process of students from outside Makassar in Business English Communication study program and their adaptability is influenced by their social nature, acceptance of differences, close relationships, empathy and support from peers and lecturers, a positive attitude, and equal opportunities for participation in campus activities.